Enhancement of countermovement jump performance using a heavy load with velocity-loss repetition control in female volleyball players - Krzysztofik, M.; Kalinowski, R.; Trybulski, R.; Filip-Stachnik, A.; Stastny, P. (International Journal of Environmental Research and Public Health, 2021)
Although velocity control in resistance training is widely studied, its utilization in eliciting post-activation performance enhancement (PAPE) responses receives little attention. Therefore, this study aimed to evaluate the effectiveness of heavy-loaded barbell squats (BS) with velocity loss control conditioning activity (CA) on PAPE in subsequent countermovement jump (CMJ) performance. Sixteen resistance-trained female volleyball players participated in this study (age: 24 ± 5 yrs.; body mass: 63.5 ± 5.2 kg; height: 170 ±6 cm; relative BS one-repetition maximum (1RM): 1.45 ± 0.19 kg/body mass). Each participant performed two different conditions: a set of the BS at 80% 1 RM with repetitions performed until a mean velocity loss of 10% as the CA or a control condition without CA (CNTRL). To assess changes in jump height (JH) and relative mean power output (MP), the CMJ was performed 5 min before and throughout the 10 min after the CA. The two-way analysis of variance with repeated measures showed a significant main effect of condition (p = 0.008; Eta2 = 0.387) and time (p < 0.0001; ?2 = 0.257) for JH. The post hoc test showed a significant decrease in the 10th min in comparison to the value from baseline (p < 0.006) for the CNTRL condition. For the MP, a significant interaction (p = 0.045; Eta2 = 0.138) was found. The post hoc test showed a significant decrease in the 10th min in comparison to the values from baseline (p < 0.006) for the CNTRL condition. No significant differences were found between all of the time points and the baseline value for the CA condition. The CA used in the current study fails to enhance subsequent countermovement jump performance in female volleyball players. However, the individual analysis showed that 9 out of the 16 participants (56%) responded positively to the applied CA, suggesting that the PAPE effect may be individually dependent and should be carefully verified before implementation in a training program.